2021
DOI: 10.1145/3457166
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Envy-freeness in Indivisible Item Allocation

Abstract: We introduce and analyze new envy-based fairness concepts for agents with weights that quantify their entitlements in the allocation of indivisible items. We propose two variants of weighted envy-freeness up to one item (WEF1): strong , where envy can be eliminated by removing an item from the envied agent’s bundle, and weak , where envy can be eliminated either by removing an item (as in the strong version) or by replicating an item from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 35 publications
4
77
1
Order By: Relevance
“…Indeed, the techniques from discrepancy theory that we used crucially rely on the additivity assumption; so does the result of Alon [1987] that established the existence of a consensus 1/k-division for divisible goods. Even in the case k = 2, where a consensus halving can be guaranteed for non-additive utilities [Simmons and Su, 2003], it is unclear whether such a halving can be rounded into a discrete allocation with a loss that is bounded only in terms of n. Beyond the setting of our paper, one could also consider allocating a mixture of indivisible and divisible goods [Bei et al, 2021] or allowing groups to have different entitlements which can correspond to the group sizes [Chakraborty et al, 2020] as well.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the techniques from discrepancy theory that we used crucially rely on the additivity assumption; so does the result of Alon [1987] that established the existence of a consensus 1/k-division for divisible goods. Even in the case k = 2, where a consensus halving can be guaranteed for non-additive utilities [Simmons and Su, 2003], it is unclear whether such a halving can be rounded into a discrete allocation with a loss that is bounded only in terms of n. Beyond the setting of our paper, one could also consider allocating a mixture of indivisible and divisible goods [Bei et al, 2021] or allowing groups to have different entitlements which can correspond to the group sizes [Chakraborty et al, 2020] as well.…”
Section: Discussionmentioning
confidence: 99%
“…When goods are indivisible and agents are symmetric, Caragiannis et al [7] showed the "unreasonable fairness" of an MNW allocation by proving that it satisfies a relaxation of EF called envy-freeness up to one good (EF1) and is PO. These desirable properties also carry over to the asymmetric case, where the MNW allocation is PO and satisfies a weighted relaxation of EF [9].…”
Section: Introductionmentioning
confidence: 93%
“…This idea has been used in models for bargaining in committees [25], maintaining fairness guarantees among ethnic groups [6], etc. From a computational viewpoint, fair division of goods to asymmetric agents is relatively less understood, but has gained interest in recent years [15,17,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are se ings where the fairness of an allocation must be considered with respect to asymmetric entitlements, e.g., in many inheritance scenarios, closer relatives have higher entitlements o en determined by law. In order to capture fairness in the presence of arbitrary entitlements, one may generalize existing notions to their weighted counterparts, like weighted MMS [Farhadi et al, 2019] and weighted EF1 [Chakraborty et al, 2021], or tweek their definitions approprietly, like in the MMS-inspired ℓ-out-of-d share of Babaioff et al [2021c]. In a recent work, Babaioff et al [2021b] introduce the notion of AnyPrice share (APS) as the maximum value an agent can guarantee to herself if she has a budget equal to her entitlement and the goods are adversarially priced with prices that sum up to 1, and show how to efficiently compute an allocation where everyone gets value no less than 3/5 of her APS.…”
Section: Arbitrary Entitlementsmentioning
confidence: 99%